Leveraging “Guilt-free Pleasure” concept in developing healthful snack products - Yu, Huizi (Kansas State University, 2020)
Consumers are seeking greater healthy and ethical living globally nowadays. The goal of this dissertation is to gain insights on promoting healthy and sustainable eating behaviors through exploring the effect of guilt on food choice and eating behaviors. In the first phase, consumer-based characteristics of food that might aid in identifying the different levels of guilt perceptions were investigated by using a qualitative approach. Product grouping patterns were identified with Sorting method based on different levels of guilt perceptions the consumers have had with 18 food and beverage products. Four categories of 45 factors were identified that could elicit guilt perceptions, including intrinsic product characteristics, extrinsic product characteristics, situational factors, and social-cultural factors, indicating its complexity and multidimensionality. Consumers' guilt tendency concerning food in the context of daily life was recognized as an essential characteristic that could influence consumers' food choices, eating behavior, purchase decisions, and lifestyle. Moreover, the product representation map implied the potential of using guilt related perceptions for product differentiation. White space of snack products that could deliver "Guilt-free pleasure" was identified, providing new opportunities for healthy snack products' development. In the second phase, a Food Consumer Guilt Scale for measuring consumers' guilt tendencies to foods was developed. A preliminary questionnaire was constructed and validated in terms of the total scale score distribution, reliability, internal validity, and discriminating ability. The updated scale with 16 items was found to be a reliable measurement instrument that showed high internal consistency, discrimination power, and was cross-validated with a new sample of consumers. Factor analysis was conducted to uncover the underlying structure of the scale, which included three aspects: (1) consumers' eating behavior, including perceived unhealthiness of food and less unhealthy eating style; (2) the naturalness of the food and its packaging; (3) a sustainable and healthy lifestyle. Consumers were identified with three different guilt tendencies related to food. They had diverse preference patterns and distinct potential eating frequency on products tested. These findings suggested that the Food Consumer Guilt Scale could be a useful segmentation tool to understand consumers' food choices and eating behaviors, therefore, helpful in providing guidance promoting healthy and sustainable eating behaviors. In the third phase, a Food Product Guilt Scale was developed to measure how product characteristics affect on products' guilt perception. A preliminary questionnaire was constructed and tested through an online survey. Reliability, discriminating ability, and correlation with the product's guilt perception was evaluated to refine the items. A final 14-item measure was found to be a reliable measurement instrument possessing discrimination power and was cross-validated with a new sample of consumers. Moreover, it was found that there was no clear relationship between guilt rating and perceived liking of the products. Regretful, Irresponsible, Lazy, Unproductive, Bloated, Heavy, Gross and Terrible were identified positively related to guilt, whereas, Healthy, Natural, Good, Balanced, Energized, Refreshed, Energetic, Productive and Sustained were negatively correlated. Product representation showed that intrinsic product characteristics of nutritional values were the main contributors to tested products' guilt perception.
Keywords: Guilt; Scale development; Food choice; Product development; Consumer segmentation